PENGARUH KONSEP DIRI DAN PERILAKU BELAJAR TERHADAP PRESTASI BELAJAR PAI DI SMAN 04 KECAMATAN KEDURANG KABUPATEN BENGKULU SELATAN - Anisatul Hasanah (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2018)
The  purpose of research  to determine whether  the  concept  of self positively  affect the  learning  achievement  of Islamic Religious Education students.  Second  Is the behavior of learning  positively affect the learning  achievement of Islamic Religious Education students,  Third Is self concept  and learning behavior have an effect on to learning achievement of Islamic Religion High School  student  of State  04  Kedurang  District of South  Bengkulu  Regency.  The  method used  in this study  is descriptive  quantitative because this research  is presented with numbers. The results showed  that self-concept  directly positive effect on  learning  achievement Islamic Religious Education In School  Mengah  Atas Negeri Kedurang  Subdistrict  of 0,379  (37,9)%,  Both Behavior of learning gives a positive influence on learning achievement of .0,670  (67,0)% Third there is influence of self concept  and behavior Learning  together  to positively influence the learning achievement of Islamic Religious Education In School Mengah  Atas Negeri 04 Kedurang  District of South  Bengkulu 0,815  (81,5) %